Effectiveness of a personalized psychocorrection program for reducing maladaptation in individuals with binge eating disorder - Sinkevych Інна (Psychosomatic Medicine and General Practice, 2025)
Introduction. Binge eating disorder (BED) is a significant medical and social problem that adversely affects patients’ physical and mental health. Traditional treatment methods (cognitive-behavioral therapy, interpersonal therapy) do not always provide a lasting effect, necessitating the development of personalized psychocorrection programs. Aim. To evaluate the effectiveness of a personalized psychocorrection program for patients with BED by analyzing changes in binge eating severity, anxiety, depression, alexithymia, and quality of life. Methods and materials. The study included 163 patients diagnosed with BED. Inclusion criteria: meeting DSM-5 diagnostic criteria for BED, age 18-65, ability to provide informed consent. Assessment tools included the BES, HADS, TAS-20, Hall Emotional Intelligence Test, and CQLS. Patients were randomized into two groups: the study group (personalized psychocorrection) and the control group (standard treatment). The dynamics were assessed on days 1, 11, 104, and 194 after the intervention. Results. Following the completion of the personalized psychocorrection program, the study group showed a statistically significant reduction in BED severity (BES, p<0.001), anxiety (HADS-A), and depression (HADS-D) levels (p<0.01). Additionally, improvements were observed in quality of life (CQLS, p<0.001) and reduced alexithymia (TAS-20, p=0.016). The control group also showed positive dynamics, but to a lesser extent. The personalized program proved to be more effective in the long-term period (6 months and 1 year later). Conclusions. The personalized psychocorrection program demonstrates high effectiveness in reducing symptoms of binge eating disorder, anxiety, depression, and alexithymia, as well as improving patients’ quality of life. It can be recommended as an effective approach to BED correction.